2007
DOI: 10.1007/s00464-007-9386-6
|View full text |Cite
|
Sign up to set email alerts
|

Signs of reperfusion injury following CO2 pneumoperitoneum: an in vivo microscopy study

Abstract: This in vivo observation demonstrated traces of reperfusion injury in liver induced by the insufflation and desufflation of CO(2 )pneumoperitoneum. The clinical relevance of this finding and the issue of using hepatoprotective substances to prevent this injury should be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
44
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 67 publications
(67 reference statements)
2
44
0
4
Order By: Relevance
“…A study by Nickkholgh et al demonstrated that pneumoperitoneum at 12 mmHg for 90 minutes induced histological (in vivo light microscopy) and biochemical (plasma liver enzyme levels) evidence of liver reperfusion injury in rats. 10 A significant increase in oxidative stress (MDA, protein carbonyls) was also observed in a rat model of laparoscopic donor nephrectomy. 33 Extra-abdominal organs also demonstrate oxidative stress with pneumoperitoneum, such as significantly increased MDA levels in rat lungs 2 and 6 h after deflation.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…A study by Nickkholgh et al demonstrated that pneumoperitoneum at 12 mmHg for 90 minutes induced histological (in vivo light microscopy) and biochemical (plasma liver enzyme levels) evidence of liver reperfusion injury in rats. 10 A significant increase in oxidative stress (MDA, protein carbonyls) was also observed in a rat model of laparoscopic donor nephrectomy. 33 Extra-abdominal organs also demonstrate oxidative stress with pneumoperitoneum, such as significantly increased MDA levels in rat lungs 2 and 6 h after deflation.…”
Section: Discussionmentioning
confidence: 91%
“…7,30,35 Pneumoperitoneum performed in rats with a pressure of 5, 10 or 15 mmHg resulted in an incremental increase in the formation of free oxygen radicals in lung and liver tissues. 36 In the study by Nickkholgh and colleagues, 10 histological and biochemical evidence of liver reperfusion injury was demonstrable at 12 mmHg but not at 8 mmHg.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Many studies have focused on changes in blood ow in intra-and extra-peritoneal organs, which is reduced during operation but is normalized a er desu ation [5][6][7]. is ischemia/reperfusion e ect leads to the overproduction of oxidants or the malfunction of the scavenging systems, postoperatively; even causing cellular damage and resultant organ dysfunction [8,9,10].…”
mentioning
confidence: 99%